Maximizing Terahertz Energy Absorption with MXene Absorber - Li, Xinliang; Luo, Hao (Nano-Micro Letters, 2023)
Achieving high absorption in broad terahertz bands has long been challenging for terahertz electromagnetic wave absorbers. Recently in Nature Photonics, Xiao et al. reported the high absorption approaching the theoretical upper limit across the whole terahertz band of MXene-based terahertz absorbers and, on this basis, constructed an applicable, updated alternating current impedance matching model. Highlights: 1 MXene film absorbers enable the near theoretical absorption strength in extremely wide wavebands of 0.5–10 THz.